(untitled) (Global Journals of Research in Engineering, 2023)
In recent years the Internet of Things has emerged as one of the most important technologies of the twenty-first century We can now connect everyday objects to the internet via embedded devices such as kitchen appliances cars thermostats and baby monitors allowing for seamless communication between people processes and things Because of low-cost computing the cloud big data analytics and mobile technologies physical things can share and collect data with minimal human intervention In this hyper-connected world digital systems can record monitor and adjust every interaction between connected things The physical and digital worlds intersect and work together By enabling connected cars IoT is reinventing the automobile The global market for connected cars is expected to grow significantly in the coming years as connectivity innovations transform the automotive industry However as with any other device that connects to the internet cyber criminals pose a threat to automotive security Personal data leaks threats to a vehicle s essential security and safety mechanisms and in extreme cases full remote control of the vehicle can all result from security breaches And as the industry moves toward more self-driving vehicles these risks are only going to grow due to increased reliance on applications connectivity and more complex and integrated electronic components Failure to address these risks could have disastrous consequences for consumer trust privacy and brand reputation Worse customer safety is jeopardized In this paper the author discusses Layer-wise Security Challenges Attack Vectors and Architectural Flaws in the Physical layer by taking an example of a device connected to Connected cars and proposes a secure architectural solution for the Internet of Things IoT that assists in delivery teams in securely designing architecting resource-intensive smart Internet of Things IoT Narrowband NIoT use cases earlier in the Life cycle by employing the Secure Design Shift Left approach